Structure and functions of Aggregation-Induced Emission-Photosensitizers in anticancer and antimicrobial theranostics - Abrahamse, Heidi; Hamblin, Michael R.; George, Sajan (Frontiers in Chemistry, 2022)
Photosensitizers with Aggregation-Induced Emission (AIE) can allow the efficient light-mediated generation of Reactive Oxygen Species (ROS) based on their complex molecular structure, while interacting with living cells. They achieve better tissue targeting and allow penetration of different wavelengths of Ultraviolet-Visible-Infrared irradiation. Not surprisingly, they are useful for fluorescence image-guided Photodynamic Therapy (PDT) against cancers of diverse origin. AIE-photosensitizers can also function as broad spectrum antimicrobials, capable of destroying the outer wall of microbes such as bacteria or fungi without the issues of drug resistance, and can also bind to viruses and deactivate them. Often, they exhibit poor solubility and cellular toxicity, which compromise their theranostic efficacy. This could be circumvented by using suitable nanomaterials for improved biological compatibility and cellular targeting. Such dual-function AIE-photosensitizers nanoparticles show unparalleled precision for image-guided detection of tumors as well as generation of ROS for targeted PDT in living systems, even while using low power visible light. In short, the development of AIE-photosensitizer nanoparticles could be a better solution for light-mediated destruction of unwanted eukaryotic cells and selective elimination of prokaryotic pathogens, although, there is a dearth of pre-clinical and clinical data in the literature.